Systematic Review: Teknologi Needle Free Jet Injection Insulin (NFJI) Efektif Mengontrol Konsentrasi Glukosa Pada Penderita Diabetes Melitus Tipe 2 - Syahrizal, Rofi; Bakar, Abu; Harmayetty, Harmayetty; Puspita Sari, Anna Juwita (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Needle-free jet injection (NFJI) is a needleless method for insulin delivery in type 2 diabetes mellitus (T2DM) patients. This study evaluates NFJI's effectiveness in controlling blood glucose. In this study, we conducted a systematic review following the PRISMA guidelines, searching six databases (EBSCO Host, ProQuest, PubMed, ScienceDirect, Scopus, and Web of Science). The search yielded a total of 379 articles. We used the following keywords: "Jet injection," "Injection Ject," "Needle-Free Injection," "Insulin," "Diabetes Mellitus Type 2," "Diabetes Type 2," "Type 2 Diabetes," and "Blood Glucose" to identify relevant studies. The aim was to investigate the effectiveness of insulin jet NFJI in controlling blood glucose levels in T2DM patients. We assessed the risk of bias using the Joanna Briggs Institute (JBI) critical appraisal tools checklist. Out of the 379 articles identified, only seven met the inclusion criteria. Among these, six articles employed the Randomized Controlled Trial (RCT) method, while one article used a quasi-experimental design. Respondents in the study consisted of T2DM patients who were divided into two research groups: the intervention group and the control group. The results indicated a significant difference in blood glucose control values between the two groups. NFJI insulin method significantly improves glucose control. It offers advantages like painless, scar-free, low drug preparation, reusability, ease of use, and minimal disease transmission. Recommended for long-term T2DM treatment.